An Evaluation of Metal cations and anions Concentration in Surface Water from Six selected areas of Coastal Guyana via Flame Atomic Spectroscopy - Jagessar R.C. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
The concentration of heavy metals such as Pb, Cu, Zn and Cd, and anions: Cl-, NO3- and SO42- and PO43- were determined for six selected surface waters of coastal Guyana . It was found that the concentration was area dependent. Cl- anion registered the highest value of 85.0 ± 1.0 mg/L at area (5). Area (3) registered a value of 0.15 ± 0.0 mg/L for NO3-. In areas such as (1) and (2), the surface waters showed negligible detection for NO3-. The highest value for SO42- , 18.95 ± 0.97 mg/L was noted for area (2). The toxic heavy metals such as Pb and Cd showed low and no detection in some areas. For Cd, this range from 0.002 ± 0.00 to 0.03 ± 0.00 mg/L, with the highest occurring at area (3). Pb was undetected in most areas. In areas of detection, the highest concentration of 0.05 ± 0.0 11 mg/L was noted. With the exception of Pb in areas (4) and (5) and Cu in area (1), the concentration of these metal ions/element and anions are below the threshold limit in surface water as accepted by International accepted standards of the Environmental Protection Agency, EPA and thus are no threat to the national livelihood. However, the country surface water must be continually tested as anthropogenic activities increases.